2005
DOI: 10.1091/mbc.e04-10-0884
|View full text |Cite
|
Sign up to set email alerts
|

A Member of the Sugar Transporter Family, Stl1p Is the Glycerol/H+Symporter inSaccharomyces cerevisiae

Abstract: Glycerol and other polyols are used as osmoprotectants by many organisms. Several yeasts and other fungi can take up glycerol by proton symport. To identify genes involved in active glycerol uptake in Saccharomyces cerevisiae we screened a deletion mutant collection comprising 321 genes encoding proteins with 6 or more predicted transmembrane domains for impaired growth on glycerol medium. Deletion of STL1, which encodes a member of the sugar transporter family, eliminates active glycerol transport. Stl1p is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
192
0
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(209 citation statements)
references
References 82 publications
8
192
0
9
Order By: Relevance
“…We consider that gpd1D gpd2D cells might import glycerol faster than wild-type cells expressing rAQP9. Possibly, the gpd1D gpd2D mutant expresses an intrinsic glycerol uptake system similar to Stl1, which mediates this enhanced uptake [18]. This in turn results in a relatively fast volume recovery and a lower Hog1 nuclear accumulation amplitude and shorter period.…”
Section: Resultsmentioning
confidence: 99%
“…We consider that gpd1D gpd2D cells might import glycerol faster than wild-type cells expressing rAQP9. Possibly, the gpd1D gpd2D mutant expresses an intrinsic glycerol uptake system similar to Stl1, which mediates this enhanced uptake [18]. This in turn results in a relatively fast volume recovery and a lower Hog1 nuclear accumulation amplitude and shorter period.…”
Section: Resultsmentioning
confidence: 99%
“…Several genes are up-regulated in response to a hyperosmotic stress. These genes include the nonessential gene STL1, which codes for a glycerol proton symporter (24,25). We decided to use its native promoter (pSTL1) to drive the expression of yECitrine, a fluorescent reporter.…”
mentioning
confidence: 99%
“…Subsequently, Oliveira & Lucas, 2004 determined that while GUP1 and GUP2 are expressed constitutively, transient changes in their expression levels in response to osmotic stress before attaining equilibrium could not be ruled out. Ferreira et al (2005), on the other hand, determined that active glycerol uptake was not attributable not either Gup1p or Gup2p but to the glycerol/H + symporter Stl1p (sugar transporter like). Recent studies have confirmed that the apparent osmosensitivity of gup1D mutants is due to the involvement of Gup1p in glycosylphophotidyl inositol lipid membrane remodelling, rather than in glycerol uptake (Yoko-o et al, 2013).…”
Section: Osmoregulation and The General Response To Environmental Stressmentioning
confidence: 99%